Specific 5'-GGGA-3'-->5'-GGA-3' mutation of the Apc gene in rat colon tumors induced by 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine. - Kakiuchi, H (1995)
The APC gene plays a major role in human colon carcinogenesis. We determined the genomic structure of the rat Apc gene, and we analyzed mutations in colon tumors induced in F344 rats by 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) and 2-amino-3-methylimidazo[4,5-f]quinoline (IQ), potent carcinogens contained in ordinary daily human food. Of eight PhIP-induced tumors, one tumor had two Apc mutations, two tumors had a mutation with loss of the normal allele, and one had a mutation. Two of the above five mutations were at nucleotide 1903, one at 2605, and two at 4237, all being a deletion of a guanine base at the 5'-GGGA-3' site and resulting in truncation of the APC protein. Of 13 IQ-induced tumors, 2 had an Apc mutation with loss of the normal allele. The two mutations were a missense mutation (T-->C) at nucleotide 1567 and a nonsense mutation (C-->T) at 2761. Alteration of the Apc gene was shown to play a more important role in PhIP-induced than in IQ-induced rat colon carcinogenesis. PhIP-induced tumors are characterized by their specific and unique mutation, which may be useful for mutational fingerprinting of human cancers.